2010
DOI: 10.1098/rsta.2010.0111
|View full text |Cite
|
Sign up to set email alerts
|

Advances in computational studies of energy materials

Abstract: We review recent developments and applications of computational modelling techniques in the field of materials for energy technologies including hydrogen production and storage, energy storage and conversion, and light absorption and emission. In addition, we present new work on an Sn 2 TiO 4 photocatalyst containing an Sn(II) lone pair, new interatomic potential models for SrTiO 3 and GaN, an exploration of defects in the kesterite/stannite-structured solar cell absorber Cu 2 ZnSnS 4 , and report details of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 214 publications
2
147
0
Order By: Relevance
“…The formation of hybrid material systems may provide an opportunity to overcome these limitations in the future. In contrast to PbO, which exhibits asymmetric Pb coordination and a low symmetry layered structure, PbS adopts a centrosymmetric rocksalt lattice with a = 5.936 Å (Madelung 2004); these structural preferences have been related to the energy separation between the Pb 6s and anion np orbitals (Walsh & Watson 2005;Payne et al 2006), with similar effects observed for other lone pair ceramics including those of Sn(II) and Bi(III) (Walsh & Watson 2004;Walsh et al 2009c;Catlow et al 2010). In its bulk form, PbS has a room temperature direct band gap of 0.420 eV at the L point of the first Brillouin zone (Madelung 2004).…”
Section: (A) Galenamentioning
confidence: 90%
See 1 more Smart Citation
“…The formation of hybrid material systems may provide an opportunity to overcome these limitations in the future. In contrast to PbO, which exhibits asymmetric Pb coordination and a low symmetry layered structure, PbS adopts a centrosymmetric rocksalt lattice with a = 5.936 Å (Madelung 2004); these structural preferences have been related to the energy separation between the Pb 6s and anion np orbitals (Walsh & Watson 2005;Payne et al 2006), with similar effects observed for other lone pair ceramics including those of Sn(II) and Bi(III) (Walsh & Watson 2004;Walsh et al 2009c;Catlow et al 2010). In its bulk form, PbS has a room temperature direct band gap of 0.420 eV at the L point of the first Brillouin zone (Madelung 2004).…”
Section: (A) Galenamentioning
confidence: 90%
“…These two materials exhibit optical band gaps of 1.7 and 3.1 eV, respectively (Turner et al 2008), covering the full range of the visible spectrum. This demonstrates the potential of hybrid materials for optoelectronic applications including photovoltaics and solid-state lighting, areas traditionally dominated by III-V, II-VI and related semiconductor alloys (Srivastava et al 1985;Wei et al 1990;Zhu et al 2008;Chen et al 2009b;Catlow et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The vacant oxygen and zinc interstitial surface sites have an important role in rationalizing the observed spectra, and the most noteworthy is the Type I mode at 1710 cm −1 for the zinc hydride stretching mode (French et al 2003a). This work along with a number of complementary studies (French et al 2001a(French et al ,b, 2003a(French et al ,b, 2004Bromley et al 2003;Catlow et al 2003Catlow et al , 2005aCatlow et al ,b, 2007Catlow et al , 2008Catlow et al , 2010Phala et al 2005;Sokol et al 2007) provided the first comprehensive computational survey of the atomistic and electronic mechanisms involved in methanol synthesis over the surfaces of pure ZnO and metal clusters supported on ZnO. Analogous methods by other groups have proved to be successful and accurate in the study of localized states and processes in a wide range of recent fundamental and applied studies (Nygren et al 1994;Mejias et al 1995;Llusar et al 1996;Rösch et al 1996;San Miguel et al 1998;de Carolis et al 1999;Kantorovich 1999Kantorovich , 2000aSushko et al 1999;Nasluzov et al 2001Nasluzov et al , 2010Karlsen et al 2003;Rivanenkov et al 2003;Danyliv & Kantorovich 2004;Mysovsky et al 2004;Seijo & Barandiarán 2004;Di Valentin et al 2006;Wang & Kantorovich 2006;Danyliv et al 2007;Giordano et al 2007;Sanz & Márquez 2007;Shor et al 2007Shor et al , 2009…”
Section: Hydrogen Dissociation Over Oxygen Terminated Polar Surface Omentioning
confidence: 98%
“…The method for calculating I consists of modelling a charged defect (in this case a hole at the top of the valence band in bulk) within a cluster of about 80 atoms treated at a QM level of theory, which is embedded in a larger cluster of about 10,000 atoms treated at a MM level of theory. The MM cluster is modelled using a polarisable shell interatomic forcefield 66 that accurately reproduces the high-frequency dielectric tensor of bulk, 12,16 so that it provides the correct polarisation response of the surrounding infinite solid to the charged defect in the QM region. In this way the defect is treated at the dilute limit.…”
Section: Solid-state Embeddingmentioning
confidence: 99%
“…9 In the context of ionic solids, a key descriptor is the Madelung potential of each crystallographic site, which is determined by a summation to infinity over the ionic charges of the surrounding ions. 10 Knowledge of the variations in the local electrostatic potential proved key to the development of theories of work functions, 11 defect chemistry including ionic conductivity, 12 and even, for example, to the understanding of the nature of hole pairing in high-temperature superconductors. 13 Since the discovery in 1972 by Fujishima and Honda 14 of the ability of TiO 2 to split water using sunlight, there has been extensive research into improving the efficiency of this process.…”
Section: Introductionmentioning
confidence: 99%